Early Visual-Spatial Integration Skills Predict Elementary School Achievement Among Low-Income, Ethnically Diverse Children. Issue 2 (17th February 2020) - Greenburg, Jordan E.; Carlson, Abby G.; Kim, Helyn; Curby, Timothy W.; Winsler, Adam
ABSTRACT: Early fine motor ability is significantly associated with later achievement, even after controlling for typical child-level predictors of school outcomes. Previous longitudinal studies have confirmed this but typically have not included low-income, at-risk populations. Research has distinguished two different aspects of fine motor skills: those that involve integrating motor information with visual-spatial information (i.e., visual-spatial integration; VSI) and those that rely mainly on coordination (i.e., fine motor coordination; FMC). This study examines the differential importance of early fine motor skills, measured during preschool, to later school performance from third through fifth grades, among a large ( n = 34, 491), primarily low-income, ethnically diverse sample of children. Research Findings : Overall, stronger VSI skills in preschool were associated with significantly better outcomes for children's standardized math and reading test scores in third, fourth, and fifth grades even after controlling for gender, SES, and preschool cognitive, language, and social-emotional skills. FMC was associated with significantly better math outcomes across all three grade levels but was not associated with better reading performance. Practice or Policy : Results indicate that VSI is a good predictor of later school achievement, whereas FMC was not as strongly associated with later achievement. Implications for early childhood intervention are discussed.